The Interaction of FABP with Kapα - Amber-Vitos, Ortal; Kucherenko, Nataly; Nachliel, Esther; Gutman, Menachem; Tsfadia, Yossi (PLOS ONE, 2015)
Gene-activating lipophilic compounds are carried into the nucleus when loaded on fatty-acid-binding proteins (FABP). Some of these proteins are recognized by the α-Karyopherin (Kapα) through its nuclear localization signal (NLS) consisting of three positive residues that are not in a continuous sequence. The Importin system can distinguish between FABP loaded with activating and non-activating compounds. In the present study, we introduced molecular dynamics as a tool for clarifying the mechanism by which FABP4, loaded with activating ligand (linoleate) is recognized by Kapα. In the first phase, we simulated the complex between KapαΔIBB (termed “Armadillo”) that was crystallized with two NLS hepta-peptides. The trajectory revealed that the crystal-structure orientation of the peptides is rapidly lost and new interactions dominate. Though, the NLS sequence of FABP4 is cryptic, since the functional residues are not in direct sequence, implicating more than one possible conformation. Therefore, four possible docked conformations were generated, in which the NLS of FABP4 is interacting with either the major or the minor sites of Kapα, and the N → C vectors are parallel or anti-parallel. Out of these four basic starting positions, only the FABP4-minor site complex exhibited a large number of contact points. In this complex, the FABP interacts with the minor and the major sites, suppressing the self-inhibitory interaction of the Kapα, rendering it free to react with Kapβ. Finally, we propose that the transportable conformation generated an extended hydrophobic domain which expanded out of the boundary of the FABP4, allowing the loaded linoleate to partially migrate out of the FABP into a joint complex in which the Kapα contributes part of a combined binding pocket.